2015
DOI: 10.1287/isre.2015.0581
|View full text |Cite
|
Sign up to set email alerts
|

Research Note—An Exploration of Risk Characteristics of Information Security Threats and Related Public Information Search Behavior

Abstract: I nformation security (IS) threats are increasingly pervasive, and search engines are being used by the public as the primary tool for searching for relevant information. This research investigates the following two questions: (1) How can different IS threats be characterized and distinguished in terms of their risk characteristics? and (2) how are risk characteristics related to public searches for information on IS threats? Applying psychometric analysis, our analyses of survey data first show that unknown r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 75 publications
(141 reference statements)
0
8
0
Order By: Relevance
“…Anxiety has received much consideration in IS research, particularly as it relates to computer anxiety (Venkatesh 2000). Although studies have consistently found a negative relationship between computer anxiety and computer self-efficacy (Compeau & Higgins 1995;Thatcher & Perrewé 2002), the role of anxiety as a discrete emotion has been noticeably absent from much InfoSec-related research (Chen et al 2012;D'Arcy et al 2014;Hwang 2005;Wang et al 2015).…”
Section: Anxiety As An Avoidance Emotionmentioning
confidence: 99%
“…Anxiety has received much consideration in IS research, particularly as it relates to computer anxiety (Venkatesh 2000). Although studies have consistently found a negative relationship between computer anxiety and computer self-efficacy (Compeau & Higgins 1995;Thatcher & Perrewé 2002), the role of anxiety as a discrete emotion has been noticeably absent from much InfoSec-related research (Chen et al 2012;D'Arcy et al 2014;Hwang 2005;Wang et al 2015).…”
Section: Anxiety As An Avoidance Emotionmentioning
confidence: 99%
“…There is demonstrable evidence that suggests that an important antecedent to security behaviors is threat perception [21,45]. Perceived threat is defined as the extent to which individuals perceive the security threat as harmful [23].…”
Section: Information Security Role Identity and Secure Behaviorsmentioning
confidence: 99%
“…Above all, it is an indicator of retailers' access to potential switchers who are actively searching for a better alternative and use comparison sites; therefore, it provides important and actionable insights to practitioners. Cross-visiting informs the scant literature on underlying mechanisms of information search (Wang et al 2015) by illustrating users' interrelated search behaviour across the network. It also adds to multichannel research as current performance outcomes are based on limited measures of cross-channel phenomenon (Cao and Li 2015).…”
Section: Conclusion and Future Research Directionmentioning
confidence: 99%
“…Then, it draws on a large-scale tracking data of million users across different websites to analyze consumers' holistic behaviour. Examining real-life logs of user behaviour is increasingly important, as it captures the actual usage rather than users' intension (Wang et al 2010) and provides valuable insight into online behaviour (Wang et al 2012(Wang et al , 2015. In addition, actual usage does not rely on participant's self-reported behaviour.…”
Section: Introductionmentioning
confidence: 99%